Dimorphism of Mandibular Canine Index Establishing in Sex Identity - Shaliputra P Magar; P V Wanjari; Tushar Phulambrikar; S P Mosby; Shilpa S Magar (Journal of Indian Academy of Oral Medicine and Radiology, 2011)
An investigation study to establish the effectiveness of using mesiodistal width of mandible and intercanine arch width in mandible in sex identity in Madhya Pradesh. The study was conducted in the Department of Oral Medicine and Radiology, Modem Dental College and Research Center, Indore. The subjects selected for the investigation included 350 individuals from rural and urban localities visiting to Modem Dental College and Research Center, and camp was conducted in school and junior college in Madhya Pradesh (MP) region. Results were statistically analyzed by using mandibular canine index (MCI), calculated by formula and observed that the mean mesiodistal width of the right as well as left mandibular canine was larger in males as compared with females. Due to accuracy and easy method, it is considered for use in sex identity.